The Relationship between Fatigue and Activities of Daily Living in Chronic Kidney Failure Patients Undergoing Hemodialysis - Zahra Khoirunnisa; Fahrun Nur Rosyid; Puji Kristini (Indonesian Journal of Global Health Research, 2024)
Patients with chronic kidney failure undergoing hemodialysis often experience decreased ability to perform activities of daily living. Fatigue is a common symptom that could influence the reduction of these activities. This study aims to analyze the relationship between fatigue and the level of independence of daily living activities in chronic kidney failure patients undergoing hemodialysis. This study used a descriptive correlative design and a cross-sectional approach with a population of 175 hemodialysis patients, which then obtained a sample of 121 people using the accidental random sampling technique. Data was collected using the FACIT Fatigue Scale and Katz index questionnaires, while the correlation test used Rank Spearman. The results showed a significant positive relationship between fatigue and the level of independence of daily living activities with a p-value = 0.001. The higher the fatigue value, the higher the level of dependence of a person on performing daily living activities. Early identification is needed to assess the fatigue status experienced by hemodialysis patients as a strategy to increase independence, which ultimately impacts quality of life.